Biosynthesis of gamma‐linolenic acid and beta‐carotene by Zygomycetes fungi. Issue 7 (7th June 2013) - Klempova, Tatiana; Basil, Eva; Kubatova, Alena; Certik, Milan
Abstract: Due to increasing demand for natural sources of both polyunsaturated fatty acids (PUFAs) and beta‐carotene, 28 Zygomycetes fungal soil isolates were screened for their potential to synthesize these biologically active compounds. Although all fungi produced C18 PUFAs, only nine strains also formed beta‐carotene. Although Actinomucor elegans CCF 3218 was the best producer of gamma‐linolenic acid (GLA) (251 mg/L), Umbelopsis isabellina CCF 2412 was found to be the most valuable fungus because of the dual production of GLA (217 mg/L) and beta‐carotene (40.7 mg/L). The calculated ratio of formed PUFAs provided new insight into activities of individual fatty acid desaturases involved in biosynthetic pathways for various types of PUFAs. The maximal activity of delta‐9 desaturase was accompanied by high accumulation of storage lipids in fungal cells. On the other hand, maximal activity of delta‐15 desaturase was found in strains synthesizing low amounts of oleic acid due to diminished delta‐9 desaturase. Activities of delta‐6 desaturase showed competition for fatty acids engaged in n 3, n 6, and n 9 biosynthetic pathways. Such knowledge about fatty acid desaturase activities provides new challenges for the regulation of biotechnological production of PUFAs by Zygomycetes fungi. Abstract : Zygomycetes fungi are well known producers of natural biologically active compounds of polyunsaturated fatty acids (PUFAs) and beta‐carotene. In this study, authors find that Umbelopsis isabellina CCF 2412 is the best producer of both gamma‐linolenic acid (GLA) and beta‐carotene out of the 28 Zygomycetes fungi strains. This is the first report describing dual production of PUFAs and beta‐carotene by microorganisms. The study of simultaneous accumulation of these metabolites may address new challenges for biotechnological overproduction of biologically active compounds.